English verb handbook - Liljeblad, Fredrik (Berlitz, 2005)
From verb basics--infinitives, imperatives, participles and more--to complete conjugations, this easy-to-use, comprehensive guide to English verbs offers clear explanations and multiple examples of usage. A perfect supplement for learners of English at all levels.